Are Canadian First Nations casinos providing maximum benefits? appraising First Nations Casinos in Ontario, Saskatchewan, and Alberta, 2006-2010 - Belanger, Yale D. (University of Nevada, Las Vegas. International Gaming Institute, 2014)
Open access article. Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND 4.0) applies To date a dearth of data has made it difficult to evaluate the success of First Nations casinos in Canada. This paper helps remedy this situation by presenting a three-province overview (Ontario, Saskatchewan and Alberta) of First Nations gaming models. Two key findings are offered that First Nations seeking gaming market entry and provincial officials should genuinely consider. First, while each province has adopted a unique approach to First Nations gaming policy they have each opted to direct substantial revenues out of First Nations communities and into their own treasuries. Second, the evidence suggests that larger gaming properties located nearby a significant market provide more benefits versus smaller properties situated in more isolated areas. The subsequent discussion elaborates each provincial model’s revenue generating power, how the revenue in question is being allocated and its corresponding socio-economic impact, whether increased problem gambling and crime have resulted as predicted, while exploring employment trends to determine whether they have developed as anticipated. Yes